Copy Number Alterations and Methylation in Ewing's Sarcoma. (15th March 2011) - Jahromi, Mona S.; Jones, Kevin B.; Schiffman, Joshua D.
Abstract : Ewing's sarcoma is the second most common bone malignancy affecting children and young adults. The prognosis is especially poor in metastatic or relapsed disease. The cell of origin remains elusive, but the EWS-FLI1 fusion oncoprotein is present in the majority of cases. The understanding of the molecular basis of Ewing's sarcoma continues to progress slowly. EWS-FLI1 affects gene expression, but other factors must also be at work such as mutations, gene copy number alterations, and promoter methylation. This paper explores in depth two molecular aspects of Ewing's sarcoma: copy number alterations (CNAs) and methylation. While CNAs consistently have been reported in Ewing's sarcoma, their clinical significance has been variable, most likely due to small sample size and tumor heterogeneity. Methylation is thought to be important in oncogenesis and balanced karyotype cancers such as Ewing's, yet it has received only minimal attention in prior studies. Future CNA and methylation studies will help to understand the molecular basis of this disease.